An aptasensor with dsDNA for rapid and highly sensitive detection of kanamycin in milk. Issue 62 (9th August 2017) - Li, Falan; Wang, Xiangyou; Sun, Xia; Guo, Yemin
Abstract : Herein, we developed an aptasensor using double-stranded DNA (dsDNA) modified with cadmium sulfide (CdS) nanoparticles and gold nanoparticles (AuNPs) on a gold electrode (GE) for kanamycin detection. Abstract : Herein, we developed an aptasensor using double-stranded DNA (dsDNA) modified with cadmium sulfide (CdS) nanoparticles and gold nanoparticles (AuNPs) on a gold electrode (GE) for kanamycin detection. The CdS nanoparticles were employed to strongly adsorb on the surface of GE via Au–S interactions. AuNPs, as the mediators, improved electron relay during the entire electron transfer process and the aptasensor response speed. Herein, we used dsDNA instead of single-stranded DNA (ssDNA) as the capture probe to prepare an aptasensor with improved stability. The proposed aptasensor exhibited a wider linearity to kanamycin in the range of 10.0–450.0 nM with a low detection limit of 2.85 nM. The aptasensor with ssDNA showed a low limit of detection of 9.76 nM. Moreover, it displayed high specificity for kanamycin and was free from interference in common milk adulterants. The proposed aptasensor had good reproducibility, stability, repeatability, and cost-effective regeneration. The aptasensor could selectively identify targets even in complex matrices, such as skimmed milk, and could be used for the detection of kanamycin in milk.